The healthy physical condition in women with breat cáncer mastectomized from the physical culture - Alina Yamilé Ayrado-Núñez; Modesta Mayo-Abraham; Fernando Jesús del Sol (Podium, 2015)
Breast Cancer is one of the leading causes of death in females, due to this doctors are working tirelessly seeking an answer to this health’s problem. That is why we plan to conduct a study reflecting from physical activity and maintaining a healthy physical condition in women with breast cancer mastectomy. There is an ethical political knowledge of scientific work which includes the idea that the same is done to meet the needs of social development, taking into account that there are no paradigms that stop scientific and technological development for the benefit and human survival. That knowledge is shared by the actors involved in technological and scientific processes; which have their roots in the social transformations that the country has experienced and the revolutionary ideology that has led. Incorporating exercises in women with mastectomies through an inclusive program from the postoperativ estage to maintenance social integration. Let’s give the women a better service to maintain a healthy physical condition,increasing the levels of survival, while we appreciate the cancer as a chronic no communicable disease and not terminal. The study can value a great economic, social and scientific impact.